Daulah Umayyah di Andalusia dan Hasil Budayanya (756-1031 M) - Itsnawati Nurrohmah Saputri (UIN Sumatera Utara Medan, 2021)
This research describes the Islamic culture during the Umayyad Daula in Andalusia. The methods used in this research are historical methods and cultural anthropological approaches. The technique used in this research is literature study, the authors collect those related to the discussion that the author did. The results of the research conducted by the Umayyad Daula in Andalusia came to power from 756-1492 AH, with the first caliph Abdurrahman Ad-Dakhil and the last caliph Muhammad XI (Nashirihyah Granada). Initially the government was led by an Amir, then at the time of Abdurrahman III it changed to Caliph. The power of the Umayyad Daula in Andalusia has several cultures, including in the field of literature, the most famous of which is Ibn 'Abd Rabbihi (860-940 AD) from Cordova, Abdurrahman III's favorite poet. In the architecture of Ad-Dakhil founded the Great Mosque of Cordova. In the field of science, a popular figure who developed the science of Fiqh in Andalusia was the writer Abu Bakr Muhammad bin Marwan bin Zuhr (d. 1031).